2007
DOI: 10.1007/s10517-007-0319-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the pharmacokinetics of a tryptophan-containing dipeptide GB-115

Abstract: Pharmacokinetics of an original compound GB-115 (N-phenylhexanoylglycyltryptophan) synthesized on the basis of the structure of endogenous tetrapeptide cholecystokinin-4 was studied by means of high-performance liquid chromatography. Pharmacokinetic parameters were calculated after intravenous and peroral administration of GB-115. Our results indicate that this dipeptide is resistant to peptidases. The absolute bioavailability of GB-115 is 4.65%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…GB-115 (N-phenylhexanoyl-glycyl-L-tryptophan amide) was synthesized at the Department of Chemistry (V. V. Zakusov Institute of Pharmacology). Pharmacological study showed that the dipeptide GB-115 is present in blood plasma after peroral administration and injection [3]. Taking into account the results of previous experiments, GB-115 was administered in doses of 0.1-10 mg/kg [6].…”
Section: Methodsmentioning
confidence: 99%
“…GB-115 (N-phenylhexanoyl-glycyl-L-tryptophan amide) was synthesized at the Department of Chemistry (V. V. Zakusov Institute of Pharmacology). Pharmacological study showed that the dipeptide GB-115 is present in blood plasma after peroral administration and injection [3]. Taking into account the results of previous experiments, GB-115 was administered in doses of 0.1-10 mg/kg [6].…”
Section: Methodsmentioning
confidence: 99%
“…These data are necessary for appropriate use of drugs: individual adjustment of the optimal therapeutic dose, treatment regimen, and permissible combination of drugs, detection of active metabolites, and prevention of adverse reactions. In this regard, experimental pharmacokinetic studies are an essential stage of preclinical trials of new drugs [1][2][3][4][5][6]9].…”
mentioning
confidence: 99%